2016
DOI: 10.20944/preprints201612.0134.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gendered Sources of Distress and Resilience among Afghan Refugees in Northern California: A Cross-Sectional Study

Abstract: Recent studies have emphasized the influence of resettlement factors on the mental health of refugees resettling in developed countries. However, little research has addressed gender differences in the nature and influence of resettlement stressors and sources of resilience. We address this gap in knowledge by investigating how gender moderates and mediates the influence of several sources of distress and resilience among 259 Afghan refugees residing in Northern California (USA). Gender moderated the effects o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 14 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…The qualitative synthesis of the gender effects on health outcomes indicated as expected that stronger adherence to traditional gender norms [62,66,70,71,77,78,81,92,94,102], higher levels of gender inequality [64,100,103], gender-based discrimination [63, 65, 67, 76, 82-88, 91, 93, 95] or gender-based violence [61,77,98] are associated with adverse health outcomes. Four studies showed that gender effects only manifested in interaction with other variables.…”
Section: Gender Effects On Health Outcomesmentioning
confidence: 97%
See 2 more Smart Citations
“…The qualitative synthesis of the gender effects on health outcomes indicated as expected that stronger adherence to traditional gender norms [62,66,70,71,77,78,81,92,94,102], higher levels of gender inequality [64,100,103], gender-based discrimination [63, 65, 67, 76, 82-88, 91, 93, 95] or gender-based violence [61,77,98] are associated with adverse health outcomes. Four studies showed that gender effects only manifested in interaction with other variables.…”
Section: Gender Effects On Health Outcomesmentioning
confidence: 97%
“…1 Flowchart of study selection process toward women [66,69,98]), 7 toward men and women (e.g. Bem-Sex-Role Inventory, sexism, double standards, sharing household responsibilities) [61,62,75,92,94,96,97], and 5 towards homosexuality [72,81,90,91]. Gender-based discrimination was almost exclusively related to sexual orientation, measuring experiences and internalisation of homosexual or transsexual stigma [63, 65, 67, 68, 72, 76, 80, 82-88, 93, 95, 99].…”
Section: Operationalisation Of Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…The present paper aims to extend knowledge in this area based on data collected between 2007–2008 from current and former Afghan refugees resettled in northern California. It is worth mentioning that in a previous publication, we used this dataset to examine gendered sources of distress [ 31 ]. Though here we examine the extent to which Afghans perceive experiencing discriminatory acts, how this affects their mental health, and whether the stress associated with perceived discrimination is moderated by the effects of pre-migration traumas and a number of post-resettlement factors.…”
Section: Introductionmentioning
confidence: 99%
“…Also, many Afghans come from regions with more 'traditional' or patriarchal gender orders that likely shape family economic strategies and women's economic integration in the US. Prior research shows that solid majorities of Afghans in the US support more egalitarian gender roles, yet there is a substantial minority of gender traditionalists, and egalitarian female Afghans may be less able to actualise their ideals than other immigrant and refugee groups (Stempel et al 2016). Finally, while we are focusing on economic outcomes in this study, we should remain cognisant of two-way causality-economic factors (unemployment, low income) may exacerbate Afghans' overall adjustment and mental distress (Bogic, Njoku, and Priebe 2015).…”
Section: Introductionmentioning
confidence: 95%